EVALUASI DAMPAK SOSIAL BANTUAN PERUMAHAN MASYARAKAT MISKIN DI KECAMATAN PREMBUNKABUPATEN KEBUMEN PERIODE TAHUN 2010-2015 - Danang Rifkianto Wibowo; R. Slamet Santoso (Journal of Public Policy and Management Review, 2018)
Prembun is one of the sub-districts targeted by housing assistance programs for the poor with the largest allocation of aid funds in Kebumen regency. The study was aimed to find out about the results of the implementation of Housing Assistance the poor and the social impact of implementing the Housing Assistance for the Poor in Prembun District. Evaluation theory by William N. Dunn was used to answer the research problems and objectives related to the results of the implementation of the housing assistance. The evaluation consists of six criteria; efficiency, effectiveness, adequacy, evenness, responsiveness and accuracy. Meanwhile, to answer the social impacts that occurred, the theory of Social Impact Analysis was used. The affected social units discussed were individual impacts, organizational impacts, community impacts, the impact of social institutions and systems. The result of the study indicates that there were still many deficiencies in the Housing Assistance for the Poor in Prembun subdistrict in Kebumen Regency. It can be seen from the results of the assistance that was not optimal. The obstacles were the executor team’s lack of understanding in the procedures for implementing the assistance, lack of participation from the community and misuse of the assistance from the poor who need help. Other problems arise related to the social impact of the assistance, such as; the lack of community self-reliance in overcoming uninhabitable houses, the lack of community awareness of the condition of uninhabitable houses and the insignificant impact of the assistance on the social interaction of the community. The result of the study is very important to be considered in the evaluation for the next Housing Assistance for the Poor Program. This recommendation is expected to help relevant agencies to improve the results of the implementation and the achievement of program objectives.